E-Farm Marketplace In Hasanah SMEs - Intan Oktaviani; Vihi Atina; Dedi Nugroho (Proceeding of International Conference on Science, Health, And Technology, 2019)
In the practice of animal husbandry there are still problems, namely the interaction of livestock actors who are less harmonious and less optimal marketing and sales of livestock. In addition, the presence of middlemen (intermediaries of farmers and consumers) in the sale of livestock products activities worsen the conditions of farmers. In this case it makes the farmers lose, because they get a small profit compared to the middlemen. Brokers are usually located in rural areas where people still lack information technology. As a result, they do not know the actual selling price of livestock products. The purpose of this research is to Design and Build an E-Farm for Livestock so that it can help improve the general economy of the community and facilitate the sharing system for livestock, livestock auctions and livestock trading. The System Development Method in this study uses the Rapid Application Development (RAD) Method. and System Design using Unified Modeling Language (UML). Testing this system uses the blackbox testing method and user testing using the questionnaire method. The results of testing through the blackbox can be concluded that the system developed can run and in accordance with expectations. The results of testing through the questionnaire obtained results for superadmin E-Farm Farms have been running well all the features in the system, for the leadership of this system can make reports, for breeders and member systems can help livestock marketing and livestock sharing systems.